Fiction and imagination how they affect public administration. - McCurdy, Howard E. (1995)
"What is the role of fiction and imagination in public sector management? It is time to consider the possibility that fiction and other forms of imagination play a larger role in public administration than previously imagined. The author suggests that fiction and imagination influence the choice of public policies and the methods for carrying them out. Fiction and imagination may even affect the meaning of "good" administration. This article examines the role of fiction and imagination in creating the popular beliefs that underlie public administration. It illustrates this process through cases on the deinstitutionalization of the mentally ill, the creation of the U.S. space program, and the effort to reform public administration through the National Performance Review"
Keywords: Public policy - United States; Bureaucracy - United States; Public administration - United States; Public administration